Plasma levels of transthyretin and retinol-binding protein in child-a cirrhotic patients in relation to protein-calorie status and plasma amino acids, zinc, vitamin a and plasma thyroid hormones - Calamita, Zamir; Dichi, Isaías; Papini-Berto, Sílvia J.; Dichi, Jane B.; Angeleli, Aparecida Y.O.; Vannucchi, Hélio; Caramori, Carlos Antonio [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 1997)
Transthyretin and retinal-binding protein are sensitive markers of acute protein-calorie malnutrition both for early diagnosis and dietary evaluation. A preliminary study showed that retinal-binding protein is the most sensitive marker of protein-calorie malnutrition in cirrhotic patients, even those with the mild form of the disease (Child A). However, in addition to being affected by protein-calorie malnutrition, the levels of these short half-life-liver-produced proteins are also influenced by other factors of a nutritional (zinc, tryptophan, vitamin A, etc) and non-nutritional (sex, aging, hormones, renal and liver functions and inflammatory activity) nature. These interactions were investigated in 11 adult male patients (49.9 ± 9.2 years of age) with alcoholic cirrhosis (Child-Pugh grade A) and with normal renal function. Both transthyretin and retinol binding protein were reduced below normal levels in 55% of the patients, in close agreement with their plasma levels of retinal. In 67% of the patients (4/6), the reduced levels of transthyretin and retinal-binding protein were caused by altered liver function and in 50% (3/6) they were caused by protein-calorie malnutrition. Thus, the present data, taken as a whole, indicate that reduced transthyretin and retinal-binding protein levels in mild cirrhosis of the liver are mainly due to liver failure and/or vitamin A status rather than representing an isolated protein-calorie malnutrition indicator.
Keywords: Liver cirrhosis; Prealbumin; Protein binding; Protein-calorie malnutrition; Vitamin A; amino acid; prealbumin; retinol; retinol binding protein; thyroid hormone; zinc; adult; alcohol liver cirrhosis; blood; human; liver failure; male; metabolism; middle aged; protein calorie malnutrition; Adult; Amino Acids; Humans; Liver Cirrhosis, Alcoholic; Liver Failure; Male; Middle Aged; Protein-Energy Malnutrition; Retinol-Binding Proteins; Thyroid Hormones; Zinc